Prinsip Doa yang Diajarkan Yesus dalam Matius 6:5-13 dan Aplikasinya bagi Pemuda Remaja - Teofilus, Joy; Situmorang, Jonar; Marini, Roberth Ruland (Sekolah Tinggi Alkitab Jember, 2026)
Prayer is an essential spiritual discipline in Christian life; however, in the digital era, the spiritual practices of youth have tended to decline in quality and often become merely routine, particularly within the context of Indonesian Christian youth. This study aimed to analyze the principles of acceptable prayer based on Matthew 6:5–13 and to examine their implications for the spiritual formation of Christian youth in Indonesia. The study was situated within the context of Indonesian Christian youth who are significantly influenced by rapid digital developments. This research employed a qualitative method using a literature study approach combined with biblical exegesis analysis. The results showed six principles of acceptable prayer: sincerity, relational orientation toward God, prioritizing God’s will, dependence on God’s provision, forgiveness, and seeking strength against temptation. The study concluded that the Lord’s Prayer contains theological and practical principles that are highly relevant for fostering spiritual resilience among Christian youth in the digital era.